Всемирный доклад о наркотиках 2012 год - United Nations Office on Drugs; Crime (United Nations, 2012)
Chapter I of this year's World Drug Report provides an overview of recent trends and the state of drug production, trafficking, and consumption, and its consequences in terms of treatment and related illnesses and deaths to drugs. Chapter II presents from a diachronic point of view the characteristics of the drug problem, its evolution and the main factors that determine it. It starts with an examination of the main features of the current problem, followed by a presentation of the changes observed in recent decades, and concludes with an analysis of the factors that have influenced its evolution and a brief overview of likely future trends.